Modeling of Kampar River Discharge as a Solitary Wave - ., Mubarak; ., . (International Journal of Engineering and Technology, 2018)
The propagation of tidal bore in Kampar River is investigated through a soliton theory.Â For far field region, the Bono wave can be treated as a solitary wave propagates on the open channel flow. The wave propagation in term of the Korteweg-deÂ Vries (KdV) equations will be described. A single soliton solution and environmental effect will be obtained. The result shows that the amplitude of tidal bore is about 5m it will have the velocity 11.6 m/s and its wavelength 30m.Â We found thatÂ the river discharge will decrease the tidal bore velocity and decay the amplitude.Â Â